A Comparison of Peer Network and Peer Video Modeling to Increase Positive Verbal Social Interactions in Young Children With Disabilities. Issue 4 (December 2018) - Oh-Young, Conrad; Filler, John; Kucskar, Maryssa; Buchter, Jennifer; O'Hara, Kathleen; Gelfer, Jeff
The ability to engage in positive social interactions is an important goal for young children with developmental disabilities (DDs). Peer-mediated intervention (PMI), one category of interventions often employed with those who show social skill deficits, involves use of typical peers who live model appropriate behaviors. A second frequent category uses videos of actors who model appropriate behaviors, video modeling (VM). There were two purposes of this study. The first was to compare the relative effectiveness of peer networking (PN), a type of PMI, and peer video modeling (PVM), a type of VM, to determine which was better at increasing the number of positive verbal social interactions performed by young children with DDs. The second was to determine whether the positive effects of the best treatment generalized to the playground. Mixed findings revealed that PN was more effective than PVM for a child with autism and for a child with language delays with evidence of generalization and that both were equally effective for a third child. Neither was effective for the fourth and fifth participants.